Analysis on Compressional Behavior of Cotton Fiber Assembly and Its Influencing Factors. Issue 14 (28th October 2022) - Yong, LI; Jian, LI; Xiaochuan, Chen; bei, Wu
ABSTRACT: Cotton fiber is a kind of cellulosic fiber and is widely used in textile. To legitimately determine the parameters of compressive force properties of cotton fiber assembly, axial stress was set up through a uniaxial quasi-static loading experiment on cotton fiber assembly. The constitutive model was built for cotton fiber assembly with viscoelastic plastic theory to calculate its mechanical parameters. The results showed that the viscoelasto plastic model was established to characterize the mechanical response. The constitutive model of stress and time had been adopted at the compression and relaxation processes. The viscoelastic constitutive model can be used to describe the densifying process. Loading cycles, compression velocity, and humidity on the parameters were also investigated by analyzing the E 1, E 2, η 2, loading cycles, and humidity showed significant influence on mechanical parameters. The E 1, E 2, and η 2 values of Stage II were lower than others because the cotton fiber assembly of Stage II was an unsteady structure. The E 1 values were almost higher than the E 2 values, the E 1, E 2, and η 2 values of Stage III and recovery were much higher than others. The senior viscoelastic stage of cotton fiber assembly mainly showed elastic deformation from loose and disordered fiber structures.